Critical study of the concept of scientific hybridization of islamic education and neuroscience - Hidayat, Kun; Suyadi, Suyadi (Universitas Negeri Jakarta, 2024)
Critical study of Islamic Education Neuroscience is still not sufficiently carried out in accounting for its knowledge, in order to confirm and fill in gaps in its scientific development. The purpose of this study is to examine the various scientific varieties of Islamic Education Neuroscience using the epistemology of Islamic Education, in order to find, fill, and develop their scientific potential, also from the perspective of developing hybridization of other Islamic Education scholarships. The method used in this study uses a qualitative type of literature according to Creswell: 2015, meaning that it is processed from various kinds of analytical theory from various sources of literature. The results of the study show that Islamic Education Neuroscience in epistemology also refers to Islamic law. Epistemologically, Irfani refers to the background of the scientific dichotomy between neuroscience, education, and Islam. Epistemologically, Burhani refers to empirical facts about the importance of collaboration between Islamic educators and neurologists in designing curricula and learning that optimizes students' brains in achieving Islamic education goals. Referring to the hybridization of other disciplines such as anthropology and psychology of Islamic education, this scientific development can further deepen the derivatives and clusters knowledge and more adapted to the needs of students.